Stakeholder views addressing the development and uptake of powered wheelchair assistive technology. (17th February 2019) - Gillham, Michael; Pepper, Matthew; Kelly, Steve; Howells, Gareth
Abstract: Purpose: The objective of this research is to identify stakeholder views with regard to the development of effective powered wheelchair assistive technologies more suited to the user and carer needs, whilst also meeting the requirements for other stakeholders, such that developers can be better guided towards producing solutions which have a better chance of getting to the market place and hence to the end user. Method: A questionnaire was designed to collect the views of all stakeholders and circulated to a statistically representative number of them. The question rating data were then checked for correlation between groups, and within groups, to establish validity. Results: The 74 stakeholders across the eight classes who responded had a good correlation between each other, with a cross class "Pearson's correlation" ranging between 0.7 and 0.95, and the "Fleiss's Kappa reliability of agreement" within each class ranging between 0.07 and 0.36. Conclusions: This research has identified that all stakeholders should be involved in the development of the technology and that some may benefit in 'role-reversal' to help understand user problems and stakeholder concerns more clearly. Cost was a significant barrier to the uptake of appropriate technology, and training of users and carers was a major issue. Furthermore, development should not increase user isolation and the impact on the user must be monitored for 'quality of life'. Technical support and training should be given to the user and their carers, and equipment must be adaptive to meet the changing needs of the user. Implications for Rehabilitation: Improved acceptance and use of technology by the user and their carers. Reduced rejection of appropriate provision. Improved mobility and interaction with others. Improved quality of life for users and carers.